The The Effectiveness of Duolingo in Speaking Skill at Al-Ikhlas Islamic Boarding School - Sefindi Aulia; Iin Baroroh Ma’arif; Yuyun Bahtiar; Hanifah Hanifah; A. Kanzul Fikri (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
English has become an essential language for communication in today’s era, including for English extracurricular students at Al-Ikhlas Islamic Boarding School Tambakberas Jombang. This study aims to measure the effectiveness of using Duolingo as one of AI chat bot technology to improve students’ speaking skill, and to explore how the implementation of Duolingo in the Islamic boarding school environment which has a limited access using electronics tool. This study used a quantitative method with quasi-experimental design, specifically non-equivalent control group design, and the data was collected from 32 female students who were devided into 2 classes (experimental class and control class), each class contain 16 female students. The results showed that students in the experimental class experienced a significant improvement in their speaking skill test than the control class. The implementation of AI chatbot (Duolingo) at the Islamic Boarding School was limited to using only two laptops due to strict electronic usage policies. Nevertheless, this study highlights the importance of integrating technology into language learning activities, emphasizing that AI-based platforms like AI chatbot (Duolingo) can enhance students’ speaking skill even within environments with restricted digital access.